(untitled) (Bangladesh Journal of Pharmacology, 2025)
The study aimed to perform the anti-diabetic potential of leaf extracts of Malvaviscus arboreus in an alloxan-treated albino rat model. Various extracts were prepared by ultrasonication-based successive extraction techniques. Six groups of albino rats (n=5 in each group) induced with alloxan received doses of plant extracts (25 mg/kg) or standard (1 mg/kg) for 14 days. Throughout the study, the blood glucose levels decreased. On day 14, n-hexane and dichloromethane extracts had mean (± SEM) blood glucose levels of 121.2 ± 2.1 and 91.6 ± 1.3 mg/mL respectively, while the extracts of ethyl acetate and methanol resulted in 119.8 ± 3.6 and 114.6 ± 6.1 mg/mL. The histopathological examination of the pancreas revealed reduced inflammation and congestion in the treated groups. Two-way ANOVA showed the level of significance of extracts of dichloromethane p=0.0002, ethyl acetate p=0.0004, methanol p=0.0058 and n-hexane p=0.0003 value. In conclusion, M. arboreus extracts show anti-diabetic activity.